COVD-17. TUMOR TREATING FIELDS FOR GLIOBLASTOMA THERAPY DURING THE COVID-19 PANDEMIC: EXPERT CONSENSUS ON USE AND EXPERIENCE. (9th November 2020) - Tosha Gatson, Na; Barnholtz-Sloan, Jill S; Drappatz, Jan; Henriksson, Roger; Hottinger, Andreas; Hinoul, Piet; Kruchko, Carol; Puduvalli, Vinay; Tran, David; Wong, Eric; Glas, Martin
Abstract: BACKGROUND: The COVID-19 pandemic has placed excessive strain on health care systems and this is especially evident in treatment decision-making for cancer patients. Glioblastoma (GBM) patients are among the most vulnerable due to increased incidence in the elderly (median age 64 years, peak between 75–84 years) and the short survival time. A virtual meeting was convened on May 9, 2020 with a panel of international neuro-oncology experts with hands-on experience using Tumor Treating Fields (TTFields). The objective was to assess the risk-to-benefit and to provide guidance for using TTFields in GBM during the COVID-19 pandemic. PANEL DISCUSSION: Topics discussed included support and delivery of TTFields during the COVID-19 pandemic, concomitant use of TTFields with chemotherapy, and any potential impact of TTFields on the immune system in an intrinsically immunosuppressed GBM population. Special consideration was given to TTFields' use in elderly patients and in combination with radiotherapy regimens (standard versus hypo-fractionated). Finally, we discussed the need to better capture COVID-19 positive brain tumor patients to analyze longitudinal outcomes and subtle changes in treatment decision-making during the pandemic. EXPERT CONSENSUS: TTFields is a portable home-use device which can be managed via telemedicine and safely used in GBM patients during the COVID-19 pandemic. TTFields has no known immunosuppressive effects and is a reliable treatment modality with a relatively favorable side-effect profile. This is important during a crisis where other treatment methods might be limited, especially for elderly patients and patients with multiple co-morbidities. It is too early to estimate the full impact of COVID-19 on the global healthcare system and on patient outcomes and strongly recommended the need to collaborate with existing cancer COVID-19 registries (i.e. CCC19, ESMO-CoCARE, etc.) to follow CNS tumor patients. These efforts would have implications in assessing lessons-learned from this crisis and future guideline development.